Peran Iklim Kerja Dan Kepemimpinan Memoderasi Pengaruh Kepuasan Kerja Terhadap Kinerja Guru (Studi Kasus SMP Negeri se Kecamatan Kajen Pekalongan) (The role of the Working Climate and Headmaster Leadership Moderating Effect of Job Satisfaction for Perform - Niti Setiasih; Yeye Susilowati (Conference In Business, Accounting, And Management (CBAM), 2012)
This research aims to analyze the role of the Working Climate and Headmaster Leadership Moderating Effect of Job Satisfaction of Performance state junior high school Teachers of Kajen district of Pekalongan Regency. In this research population of 107 people, while the sample was taken as many as 92 people as respondents with a purposive sampling method. Testing the hypothesis in this study using regression analysis. Results of the research can be summarized as follows: (i) Job Satisfaction does not have a positive and significant impact of teacher performance., (ii) Working Climate positive and significant impact of teacher performance, (iii) Headmaster leadership did not have a positive and significant impact on teacher performance, (iv) Working Climate is unknown moderating or not memoderate of Job Satisfaction influence for Teacher Performance, (v) Headmaster Leadership is unkwown moderating or not memoderate of Job Satisfaction for Teacher Performance.Keywords: Working Climate, Headmaster Leadership, Job Satisfaction and Teacher Performance.